PEMODELAN PEMILIHAN JENIS PENDIDIKAN SEKOLAH TINGKAT SMA SEDERAJAT DI KEL. POGAR KEC. BANGIL MENGGUNAKAN REGRESI LOGISTIK MULTINOMIAL - Heriyansyah, Dwi; Sulistiyawan, Edy (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2017)
Equal high school education is broadly divided into three types of education namely; General education, vocationaleducation and religious. A study was conducted on 200 children with status as equivalent high school students in Kelurahan Pogar, Kecamatan Bangil District by using multinomial logistic regression analysis to determine the tendency of school type selection. This study uses seven predictor variables are; sex (X1), father education (X2), mother education (X3), father work (X4), mother work (X5), child status (X6) and family status (X7). Based on the result of multinomial logistic regression analysis simultaniously, it is know that only one variable can be used as a model significanly that is sex variables and obtained logit model of _sex(male). Probability for the selection of public school education types based on male sex are 0,06 and the probability of choosing the type of vocational school education based on male sex is 0,94. When viewed from the value of the odds ratio (Exp(B)), it can be concluded that the tendency for the selection of the type of vocational school education for the male is 2,851 times greater than the female sex.